Dairy microbiology : a practical approach - Papademas, Photis (Taylor and Francis, 2015)
The objective of this book is to provide a scientific background to dairy microbiology by re-examining the basic concepts of general food microbiology and the microbiology of raw milk while offering a practical approach to the following aspects: well-known and newfound pathogens that are of major concern to the dairy industry. Topics addressed include Cronobactersakazakii and its importance to infant formula milk or Mycobacterium avium subspecies paratuberculosis (MAP) that might be connected to chronic human diseases (Crohn's), the role of dairy starter cultures in manufacturing fermented dai.